2019
DOI: 10.21203/rs.2.10258/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Mycoplasma pneumoniae Loads and Persistent Long-term Mycoplasma pneumoniae DNA in Lower Airway Associated with Severity of Pediatric Mycoplasma pneumoniae Pneumonia

Abstract: Background: An increased number of refractory mycoplasma pneumoniae (MP) pneumonia (MPP) cases have been reported. However the duration of MP infection in lower airway and the course of anti-MP treatment remains unclear. Methods: We retrospectively reviewed the medical records of 94 MPP children. Patients were classified into two groups. The long-term group (Group LT) was defined as bronchoalveolar lavage fluid (BALF) remained MP-positive by PCR after 30 days of the disease course. The non-long-term group (Gro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Yang et al reported corticosteroid therapy might prevent disease progression, and anti-MPantibiotics may have limited effects on MPP [1] . We agree with the above opinions that even timely macrolidesusceptible antibiotics such as moxi oxacin couldn't prevent disease progression through clinical experience [14] , so we didn't highly focus on the anti-MP treatment in this study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Yang et al reported corticosteroid therapy might prevent disease progression, and anti-MPantibiotics may have limited effects on MPP [1] . We agree with the above opinions that even timely macrolidesusceptible antibiotics such as moxi oxacin couldn't prevent disease progression through clinical experience [14] , so we didn't highly focus on the anti-MP treatment in this study.…”
Section: Discussionmentioning
confidence: 64%
“…To our knowledge, only a few studies mainly Chinese studies have reported of the effective and well-tolerated BLT and bronchoscopy ndings such as mucus plugs on the early stage of RMPP [14,17,[26][27][28] . It has been reported that airway hypersecretion, epithelial desquamation, and remodeling cause AO in a human airway epithelium model with M. pneumoniae infection [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid could effectively initiate the rapid improvement of clinical symptoms and chest radiographic findings, however its resistant has been reported in some RMPP patients with more severe presentations and more serious radiological finding 8 . In the near ten years, RMPP and SMPP are very common in North China particularly in our hospital, which have much higher sequelae rate mainly BO 2,[4][5][6] . Thus, there is an urgent need to discover serum biomarkers and target drugs for monitoring the progress and prevent airway remodeling of SMPP.…”
Section: Introductionmentioning
confidence: 79%
“…The clinical presentation of mycoplasma pneumoniae (MP) pneumonia (MPP) includes pulmonary symptoms like bronchiolitis and pneumonia even necrotizing pneumonia, thrombosis, and the extra-pulmonary symptoms such as encephalitis, and hemolytic anemia. Persistent MP infection, airway obstruction and airway remodeling have been concerned in human airway epithelium, BALB/c mice, and SMPP children [1][2][3] . MPP patients may develop into severe life-threatening pneumonia (severe MPP, SMPP) with features of respiratory failure and acute respiratory distress syndrome, and sequelae such as atelectasis and bronchiectasis due to bronchiolitis/bronchitis obliterans (BO) resulting from airway remodeling 2,[4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation of Mycoplasma pneumoniae (MP) pneumonia (MPP) includes pulmonary symptoms, such as bronchiolitis, pneumonia or necrotizing pneumonia, thrombosis, and extrapulmonary symptoms, such as encephalitis and hemolytic anemia. Persistent MP infection, airway obstruction, and airway remodeling have been reported in the airway epithelium of BALB/c mice and children with severe MPP (SMPP) [1][2][3]. Patients with MPP may develop life-threatening SMPP with respiratory failure, acute respiratory distress syndrome, and sequelae such as atelectasis and bronchiectasis caused by bronchiolitis/bronchitis obliterans (BO), which results from airway remodeling [2,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%